Tourism development in border areas: a benefit or a burden? The case of Karelia - Stepanova, S. V. (Baltic Region, 2019)
Border regions are expected to benefit from their position when it comes to tourism development. In this article, I propose a new approach to interpreting the connection between an area’s proximity to the national border and the development of tourism at the municipal level. The aim of this study is to identify the strengths and limitations of borderlands as regards the development of tourism in seven municipalities of Karelia. I examine summarised data available from online and other resources, as well as my own observations. Using median values, I rely on the method of content analysis of strategic documents on the development of cross-border municipalities of Karelia. My research focuses on the tourism and recreation potential of borderlands and analyses the development of local tourism infrastructure. I describe the major types of tourism, examine tourist flows, and consider the strategic aspects of tourism at the municipal level. I identify the strengths and limitations of the development of tourism in border areas by comparing the data on border and inland municipalities of Karelia and investigate the role of international border crossing points in the development of tourism in borderlands.